“I used to think … and now I think!”: Notes from a South African teacher educator (Yesterday & Today Journal for History Education in South Africa and abroad, 2023)
What is the role of the school and the teacher in the context of democratic social transformation? How has it changed globally and in the South African context during the past fifty years? Is there room for optimism among teacher educators in the 21st century? I offer some modest reflections on my own career in the hope of provoking some debate from colleagues.“A life history is a life story located within its historical context.” (Ivor Goodson)“I used to think that public school were vehicles for reforming society. And now I think that while good teachers and schools can promote positive intellectual, behavioral and social change in individual children and youth, [American] schools are (and have been) ineffectual in altering social inequalities.” (Larry Cuban).“Nearly half century of experience in schools and the sustained research I have done have made me allergic to utopian rhetoric.” (Larry Cuban)
Keywords: History of Education; Autobiography; South Africa; Teacher education; History education; Educational policy; Apartheid; Historiography